Factors limiting early life stage survival and growth during endangered Wyoming toad reintroductions. Issue 3 (28th December 2015) - Polasik, Julia S.; Murphy, Melanie A.; Abbott, Tyler; Vincent, Kim
ABSTRACT: Understanding the limiting factors of recovery is essential for guiding sound management of endangered species. The Wyoming toad ( Anaxyrus baxteri ) is a critically endangered amphibian whose cause of decline and inability to reestablish breeding populations despite early life stage reintroductions remains unknown; habitat degradation and the pathogen Batrachochytrium dendrobatidis ( Bd ) are 2 potential contributing factors. In 2013, we experimentally tested the effects of habitat factors under food‐supplemented and predator‐protected conditions (i.e., mesh field enclosures) on time to metamorphosis, the proportion of tadpoles that metamorphosed, tadpole and toadlet size, the proportion of toadlets remaining in enclosures at release (approx. 1 month post‐metamorphosis), and Bd prevalence in early life stages of Wyoming toads at Mortenson Lake National Wildlife Refuge. In 2014, we tested the effects of small‐scale application of vegetation height management on toadlet size, the proportion of toadlets that remained, and Bd prevalence until 1 month post‐metamorphosis. In 2013, median time to metamorphosis (25.5 days) was shorter in warmer water temperatures and proportion of tadpoles that metamorphosed was 0.70. In 2013, toadlet size was positively related to forb cover up to 35% and although overall treatment effect was not significant, mid‐vegetation height treatments (10–30 cm) had fewer small toadlets at release than short (0–10 cm) and tall (>30 cm) vegetation heights. In 2014, vegetation height treatment (11.49–31.6 cm) had marginal support for estimating larger size at release. Batrachochytrium dendrobatidis was not detected in water samples or on post‐metamorphic toadlets. Our results suggest that in mesh field enclosures, time to metamorphosis is shorter in warm water. In addition, vegetation heights of 10–30 cm and up to 35% forb cover within terrestrial mesh enclosures could increase Wyoming toad post‐metamorphic size, which could increase overwinter survival rates. Using mesh field enclosures for soft‐release may improve the effectiveness of early life stage reintroduction efforts, but predator attraction and density‐dependent growth need to be considered. Habitat management can also influence growth and survival of early life stages of amphibians and may benefit reintroduction efforts for other species. © 2015 The Wildlife Society.